The effect of exercise intervention on atherosclerosis prevention in overweight or obese adults: A Bayesian network meta-analysis of randomized controlled trials - ChunBaiXue Yang; Yang Xu; XiuPeng Li; HangLin Yu; Mingrui Wang; Bing Yang (PLoS ONE, 2026)
Background Obesity is a major modifiable risk factor for atherosclerotic cardiovascular disease. This study evaluated the efficacy of different exercise modalities in improving vascular health parameters in overweight/obese adults. Methods We conducted a systematic review and network meta-analysis of 51 randomized controlled trials (n = 2638) following PRISMA and a prospectively registered PROSPERO protocol (CRD420251066443). PubMed, Web of Science, the Cochrane Library, and EBSCO SPORTDiscus were searched from inception to 31 May 2025, supplemented by Google Scholar and reference screening. Eligible trials enrolled adults aged 18–65 years with overweight/obesity, included interventions lasting ≥4 weeks, and compared CET, RT, INT, CT, or HYB with usual lifestyle/standard care. The primary outcome was FMD, with CIMT and PWV as secondary outcomes. Risk of bias was assessed using RoB 2 and certainty of evidence using CINeMA. Effects were synthesized as SMDs with 95% CIs, and modalities were compared using network meta-analysis. Results The certainty of evidence was assessed using CINeMA, with a low confidence rating. Fifty-one trials (n = 2,638) met the inclusion criteria. Compared to the control group, exercise interventions led to significant improvements in Flow-Mediated Dilation (FMD) (SMD = 0.99, 95% CI 0.69–1.29), reductions in Pulse Wave Velocity (PWV) (SMD = −0.31, 95% CI −0.44 to −0.18), and decreases in Carotid Intima-Media Thickness (CIMT) (SMD = −0.20, 95% CI −0.36 to −0.05). Network meta-analysis revealed that HYB was most effective for improving FMD, INT was most effective for reducing PWV, and CET and RT exhibited similar effects on CIMT. Subgroup analyses indicated that the effects were more pronounced in women and in Asian populations. Conclusions Exercise interventions improve vascular health in overweight/obese adults, with modality-specific patterns across vascular domains. HYB appears most favorable for enhancing endothelial function (FMD), INT may offer greater benefits for reducing arterial stiffness (PWV), and both CET and RT show comparable effects on structural remodeling (CIMT).